Contour Tracking Control for High-Order Fully Actuated Multi-Axis Motion Control Systems - Wu, Qi; Hua, Chengyuan; Gu, Caoyuan; Wang, Yao-Wei; Zhang, Wen-An; Takagi, Shigeyuki (IEEE International Conference on Industrial Technology (Online), 2025)
This paper investigates the contour tracking control problem for a class of multi-axis motion control systems (MAMSs) with parameter uncertainties and external disturbances. First, a high-order fully actuated (HOFA) tracking error model of the MAMSs is established, and a fully actuated controller is designed to transform it into a linear constant system model with arbitrarily configurable poles. Second, parameter uncertainties and external disturbances are regarded as lumped disturbances of the system according to the concept of equivalent input disturbance (EID), and a generalized extended state observer (GESO) is designed to estimate the lumped disturbance. Then, the tracking controller for the single-axis is designed via the model predictive control (MPC) method in order to compensate for the disturbance effect through a feed-forward control method. On this basis, a cross-coupled control (CCC) strategy is used to further compensate the contour tracking error of MAMSs. The effectiveness of the proposed method are verified through a simulation of a two-axis motion control system.